The Physical and Sensory Qualities of ‘Lakatan’ Banana (Musa acuminata) in Response to Different Natural Ripening Agents - Karl Fritze Sibay Sampiano; April Jeanne E. Durban (Food, Agriculture and Natural Resources - NETWORKS, 2022)
‘Lakatan’ banana is amongst the most important banana varieties in the Philippines. This variety of bananas is widely known and cultivated due to its good sensory qualities and potential for the export market. Locally, ‘Lakatan’ banana is ripened by retailers through the use of calcium carbide and/or ethephon. However, these ethylene-producing chemicals were reported to cause poisoning and alter the fruit's taste. This study is designed to investigate the effects of natural ripening agents such as plant leaves on the ripening qualities and sensory attributes of ‘Lakatan’ banana under room conditions. The result results revealed that C. muconoides and F. septica significantly induced faster ripening of banana as compared to other treatments. Additionally, the disease severity of ‘Lakatan’ banana was lower in both leaves as compared to other treatments. On the other hand, bananas treated with C. muconoides, F. septica, and A. carambola leaves were found to have a longer marketable days. In terms of sensory quality, fruits treated with C. mucunoides, G. sepium, and A. carambola leaves were found to have high sensory acceptability. The results have concluded that leaves of C. muconoides, F. septica, G. sepium and A. carambola have great potential in ripening climacteric fruits like bananas, and these leaves are good substitutes for chemical ripening agents. The research highlights the need for further studies on the biological sources of ethylene to understand its advantages, including its limitations.